Homocystamide Conjugates of Human Serum Albumin as a Platform to Prepare Bimodal Multidrug Delivery Systems for Boron Neutron Capture Therapy - Popova, Tatyana; Dymova, Maya A.; Koroleva, Ludmila S.; Zakharova, Olga D.; Lisitskiy, Vladimir A.; Raskolupova, Valeria I.; Sycheva, Tatiana; Taskaev, Sergei; Silnikov, Vladimir N.; Godovikova, Tatyana S. (Molecules (Basel, Switzerland), 2021)
Boron neutron capture therapy is a unique form of adjuvant cancer therapy for various malignancies including malignant gliomas. The conjugation of boron compounds and human serum albumin (HSA)—a carrier protein with a long plasma half-life—is expected to extend systemic circulation of the boron compounds and increase their accumulation in human glioma cells. We report on the synthesis of fluorophore-labeled homocystamide conjugates of human serum albumin and their use in thiol-‘click’ chemistry to prepare novel multimodal boronated albumin-based theranostic agents, which could be accumulated in tumor cells. The novelty of this work involves the development of the synthesis methodology of albumin conjugates for the imaging-guided boron neutron capture therapy combination. Herein, we suggest using thenoyltrifluoroacetone as a part of an anticancer theranostic construct: approximately 5.4 molecules of thenoyltrifluoroacetone were bound to each albumin. Along with its beneficial properties as a chemotherapeutic agent, thenoyltrifluoroacetone is a promising magnetic resonance imaging agent. The conjugation of bimodal HSA with undecahydro-closo-dodecaborate only slightly reduced human glioma cell line viability in the absence of irradiation (~30 μM of boronated albumin) but allowed for neutron capture and decreased tumor cell survival under epithermal neutron flux. The simultaneous presence of undecahydro-closo-dodecaborate and labeled amino acid residues (fluorophore dye and fluorine atoms) in the obtained HSA conjugate makes it a promising candidate for the combination imaging-guided boron neutron capture therapy.